Laparoscopic partial circular myectomy for congenital esophageal stenosis due to tracheobronchial remnant. Issue 4 (21st January 2020) - Mochizuki, Kyoko; Shinkai, Masato; Kitagawa, Norihiko; Usui, Hidehito
Abstract: Congenital esophageal stenosis (CES) is a rare anomaly, and its appropriate management is not well established. This may be the first report describing laparoscopic partial circular myectomy of the esophageal wall in an infant with CES caused by tracheobronchial remnant (TBR). The narrow segment of the esophagus was laparoscopically detected 1 cm above the esophagogastric junction because the segment was whiter and narrower than the other parts of the esophagus. The narrow segment was approximately 1.5 cm in length. Partial anterior 270° circular muscle layers were dissected using hook electrocautery. Small cartilage‐like tissues were identified during the procedure. The muscular layers of both ends were interruptedly sutured. Intraoperative complications were not detected. After undergoing balloon dilation for slight residual stenosis, the patient could eat solid foods without vomiting. Laparoscopic partial circular myectomy is safe and effective for short‐segment lower esophageal stenosis in patients with CES caused by TBR.